Chinese immigrant parents as home teachers : maintaining and developing children's heritage language in New Zealand : a thesis presented in partial fulfillment of requirements for the degree of Master of Education in Arts and Language at Massey University - Lu, Lin (Massey University, 2003)
This research investigated Chinese immigrant parents as home teachers maintaining and developing children's heritage language in New Zealand. The case study approach was employed to enable rich information to be obtained. Data was collected from eight recent Chinese immigrant families and their children by means of non-participant observations and interviews. From my research, I found Chinese immigrant parents defined bilingualism as both their children's first and second language. I also found that these immigrants who immigrated to New Zealand under the Points System were highly educated in China and maintained a strong subconscious belief in the Confucian ideas. As the descendants of Confucianism, Chinese immigrant parents have positive attitudes towards their children's bilingualism and highly value education. They set up a home Chinese teaching and learning context so they can pass on the Chinese language and culture. A major finding of this study is that children have a positive attitude towards their heritage language maintenance and development, even though there is a strong influence from the reality of living in an English dominated country and receiving English formal education. The main reason for this outstanding result seen in these children's bilingual development is because of their parents' great efforts to offer teaching in Chinese at home. The results are illustrated as a tree to demonstrate that the traditional Chinese Confucian ideas, and the impact of Chinese parents' perceptions of bilingualism and reality in New Zealand. The Confucian ideas are shown as the roots of the tree that support and nurture the expectations of Chinese parents' perceptions. The trunk illustrates the contribution from the parents as home teachers. The three main branches stand for parents' opinions, and the outcome of the children's attitudes is presented by the leaves surrounding the branches.
Keywords: New Zealand; Chinese; Chinese language; Bilingualism